Preventing Domestic Violence Under Martial Law in Ukraine - Haltsova, Olena; Obolentsev, Valeriy; Smetanina, Nataliia; Fivkin, Petro; Panova, Svitlana (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
The issue of domestic violence is one of the most common violations of human rights in modern times. No nation is exempt from this issue. However, the conflict and its aftermath have only exacerbated the situation and complicated it, although domestic violence has long been a serious and widespread problem in Ukrainian society. Therefore, research and analysis of this harmful social phenomenon is necessary to successfully combat domestic violence, especially in light of martial law. The combination of statistical data collection and analysis, analysis, synthesis, induction and deduction, dialectical and analytical approaches, abstraction, and generalization formed the basis of the methodology of the research. This study aims to analyze the current situation and statistics surrounding domestic violence in Ukraine during the period of war, to discuss the problem of preventing domestic violence under martial law, and to give recommendations for strengthening the laws governing this area.